Conflict management strategies: the role of personality and specific social relation beliefs in Serbia and Italy - Džamonja Ignjatović Tamara; Petrović Danijela S.; Kosić Ankica; Dimoski Jana; Knežević Goran (Psihološka Istraživanja)
This study explores the relationships among conflict management strategies, personality traits, and beliefs about social relations in Italy and Serbia. These two European countries are geographically close, but have different histories, traditions and religions, and they differ along the individualistic-collectivistic dimension. Goals: The study aims to explore and compare the way in which basic personality dimensions predict specific conflict management strategies, as well as the way in which the Competitive Jungle worldview and the beliefs about conflicts mediate their relationship in different cultures. Method: The sample comprised 764 young people, aged 18-30 (M=21.54, SD=2.80). The measures included the Dutch Test of Conflict Handling, Mini IPIP-6, Delta personality inventories, Competitive Jungle Worldview and Conflict Beliefs scales. Path analyses were applied with seven personality traits as predictors (Neuroticism, Extraversion, Openness, Agreeableness, Conscientiousness, Honesty, and Disintegration), two social relation beliefs as mediators, and three conflict management strategies (Cooperative, Defensive, and Competitive) as criterion variables. Results: The results indicate that the common predictors are Openness and Agreeableness for the Cooperative strategies, Agreeableness and Disintegration for the Defensive strategies, and Extraversion for the Competitive strategies. Neuroticism and Conscientiousness are not implicated in conflict situations, while Honesty and Disintegration have a different impact on this form of behaviour in these two cultures. The results have confirmed different pathways of personality traits through the beliefs about the world as a competitive jungle and the beliefs about conflicts as threats or challenges. Conclusion: Basic personality traits, as universal dispositions for behaviour, have similar effects on conflict management strategies in both countries, while differences are observed in the mediating role of beliefs, which are shaped by the cultural differences existing between Serbia and Italy